Pengaruh Adopsi Teknologi, Peran Pemerintah, Kompetensi, Luas Lahan, dan Kelembagaan Terhadap Kesejahteraan Buruh Tani di Desa Pancasari Kecamatan Sukasada - Kencani, Kadek Dena Ayu; Irwansyah, M. Rudi (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
The aim of this research is to examine the influence of technology adoption, government role, competency, land area and institutions on the welfare of farm workers in Pancasri Village, Sukasada District. The research location was carried out in Pancasari Village involving 32 farm workers as respondents. The sampling technique used is a saturated sampling technique, with multiple linear regression analysis techniques. The process of testing the hypothesis using the t test and f test using SPSS 25.0 for Windows, the research results show that Technology Adoption has no effect on the welfare of farm workers, while the Role of Government and Competence has an effect on the welfare of farm workers, Land Area has no effect, and Institutions have no effect on welfare of farm workers in Pancasari Village, Sukasada District. So it can be concluded that income does not mediate technology adoption, land area or institutions on welfare.